Public - Private Partnership in agroforestry venture : Issues and reflections - Thukral, Neeru (Indian Journal of Agroforestry, 2020)
Experiences of working for the last four decades for agroforestry has now well recognized and understood its significance for environmental security and sustainable development in the country. Agroforestry is, thus, viewed as a profitable portfolio, compared to agriculture alone, and need be recognized as venture. The increasing demand of technical and managerial skills and investment for this ecological - economic venture can not be met by the public sector alone from its public-based resources. Public-private partnership (PPP or P3) is, therefore, recommended as desirable option to supplement the efforts of public sector. The P3 bridges the gaps through availability of modern technology, private investment flows, efficient use of resources, better project designs and implementation and effectiveness gains. It leads to faster implementation, reduced life-cycle costs and optimal risk allocation. This contribution puts forward some potential ways and means for effective P3 in agroforestry venture, and also identifies the future policy needs and R & D expectations. Formulation of a nation-wide agroforestry policy considering the regional imbalances, interface issues and P3 in business perspective is urgently called for.